BigA is a novel adhesin of Brucella that mediates adhesion to epithelial cells - Czibener, Cecilia (2015)
Adhesion to cells is the initial step in the infectious cycle of basically all pathogenic bacteria, and to do so, microorganisms have evolved surface molecules that target different cellular receptors. Brucella is an intracellular pathogen that infects a wide range of mammals whose virulence is completely dependent on the capacity to replicate in phagocytes. Although much has been done to elucidate how Brucella multiplies in macrophages, we still do not understand how bacteria invade epithelial cells to perform a replicative cycle or what adhesion molecules are involved in the process. We report the identification in Brucella abortus of a novel adhesin that harbours a bacterial immunoglobulin-like domain and demonstrate that this protein is involved in the adhesion to polarized epithelial cells such as the Caco-2 and Madin-Darby canine kidney models targeting the bacteria to the cell-cell interaction membrane. While deletion of the gene significantly reduced adhesion, over-expression dramatically increased it. Addition of the recombinant protein to cells induced cytoskeleton rearrangements and showed that this adhesin targets proteins of the cell-cell interaction membrane in confluent cultures.